The impact of climate hazards to airport systems: a synthesis of the implications and risk mitigation trends - Voskaki, Asimina; Budd, Thomas; Mason, Keith (Taylor & Francis, 2023)
Climate hazards have only fairly recently been acknowledged as key risk factors for airports. While there is a growing body of research examining specific climate change impacts, there is only limited work that combines this literature with overall climate risk. This paper seeks to address this gap in the literature by investigating and synthesising findings from studies relating to historical airport sensitivity to climate hazards and offering insights on the overall climate risk for the global airport system. With airports increasingly needing to become more “climate-resilient” due to projected changes in global climate, airport planners and decision-makers face challenges in terms of identifying key priority areas for resilience planning and investment. The findings of the paper provide insights into these challenges by examining best-applied practices and current levels of vulnerability. The paper supports the wider inclusion of climate risks as a key factor in airports’ planning and operational processes. This will require transforming current management cultures to enhance an airport's operational ability to respond to climate events efficiently and recover quickly in the event of a disruption.
Keywords: Airports; Airport systems; Climate hazard; Climate risk; Climate resilience; Climate change adaptation